1996
DOI: 10.1080/02688699647393
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of BOP-B graft orally following anterior cervical discectomy and fusion

Abstract: Graft extrusion following anterior cervical discectomy and fusion is a recognized complication. We report a case of oral extrusion of a synthetic graft (BOP B, Biocompatible Orthopaedic Polymer).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Risk factors for cervical graft failure and instrumentation migration include inadequate purchase of screws, 9 malposition and poor screw purchase, 2,8,9 poor postoperative immobilization of spine, 8,12 incomplete fusion, 9 multilevel involvement, 2 and medical illnesses contributing to poor tissue healing. 12 These risk factors were derived mainly from case reports, and no randomized trials have been performed to delineate the relative contributions from the various factors sited.…”
Section: Risk Factors and Hypothesized Mechanism Of Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors for cervical graft failure and instrumentation migration include inadequate purchase of screws, 9 malposition and poor screw purchase, 2,8,9 poor postoperative immobilization of spine, 8,12 incomplete fusion, 9 multilevel involvement, 2 and medical illnesses contributing to poor tissue healing. 12 These risk factors were derived mainly from case reports, and no randomized trials have been performed to delineate the relative contributions from the various factors sited.…”
Section: Risk Factors and Hypothesized Mechanism Of Injurymentioning
confidence: 99%
“…There have been a number of case reports documenting migration and oral or esophageal extrusion of anterior cervical screws, grafts, and plates. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In different reports, screws were recovered in feces, embedded in the abdomen, or coughed out externally. Although potentially serious or fatal, 7 of 8 patients with oral extrusion of graft or instrumentation had benign courses and uneventful recovery.…”
Section: Incidence Of Cervical Instrumentation Failure Esophageal Pementioning
confidence: 99%
See 1 more Smart Citation
“…The most catastrophic event was recently described by Riew et al who reported a case of plate rupture and graft migration causing airway impairment and resulting in death of the patient 16) . The extrusion of a cervical graft has been described in the literature on only a few occasions : the oral graft extrusion of an iliac crest donor, and the oral extrusion of a screw and of a synthetic graft 5,6,14,20) . Ours is an extremely rare case in which an expansion screw from a cervical spine locking plate migrated and was extruded orally.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia is a recognized presentation. 1 To date, no life-threatening complications of graft extrusion have been reported. We present a case of acute laryngeal obstruction due to extruded graft.…”
Section: Introductionmentioning
confidence: 99%